Are the lakes and rivers of Dhaka city safe for water-based recreation? A case study of Salmonella spp. - Chakma, Tanmoy (Brac University, 2019)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Biotechnology, 2018.